Analisa Getaran Pada Balok Jepit Bebas dan Jepit-Jepit dengan Variasi Posisi Motor Penggetar - Faisal, Muhammad; Endriatno, Nanang; Sudia, Budiman (Teknik Mesin Universitas Halu Oleo, 2021)
This study aims to determine the difference in vibration produced when the position of the vibration source is placed in a different position on the cantilever beam which is supported by fixed-fixed and free-fixed supports. This research used 6061 series aluminum beam with a size of 32 mm x 32 mm x 600 mm. Variations the placement of the exciter of fixed-fixed beams was in the 15 cm, 30 cm, and 45 cm positions, while the fixed-free beams was in the 10 cm, 20 cm, 30 cm, 40 cm, and 50 cm positions. The results of the research on fixed-fixed beams showed that the maximum displacement value was at a position of 30 cm with a value of 0.097 mm, the minimum displacement at 45 cm with a value of 0.04 mm. The maximum velocity value was at a position of 15 cm with a value of 0.653 cm/s, the minimum velocity was at a position of 45 cm with a value of 0.397 cm/s. The maximum acceleration value was at a position of 15 cm with a value of 12.16 m/s², the minimum acceleration was at a position of 45 cm with a value of 8.33 m/s². While the fixed-free beam showed that the maximum displacement value was at a position of 50 cm with a value of 0.197 mm, the minimum displacement at a position of 10 cm with a value of 0.097 mm. The maximum velocity value was at a position of 30 cm with a value of 1.138 cm/s, the minimum velocity at a position of 10 cm with a value of 0.670 cm/s. The maximum acceleration value was at a position of 30 cm with a value of 21,833 m/s², the minimum acceleration was at a position of 10 cm with a value of 9.95 m/s².Keywords: vibration, displacement, velocity, acceleration, aluminum